Miners' strike - Italian newspaper, 1984 (London, 1984)
1984 1980-95 "Miners' strike - Italian newspaper, 1984" [BW0151], 1984, Trades Union Congress The Italian union federation CGIL-CISL-UIL in the Emilia-Romagna region published this special edition of the Yorkshire Miner to support the National Union of Mineworkers strike. The paper also reports that almost 34 million lire had been collected in Italy to support the strike.